QOL-53. METFORMIN RESULTS IN HIPPOCAMPAL REMODELING AND IMPROVED MEMORY ENCODING IN PAEDIATRIC BRAIN TUMOR SURVIVORS TREATED WITH CRANIAL RADIATION: A PILOT RANDOMIZED CONTROLLED CROSSOVER STUDY. Issue 2 (22nd June 2018) - Ayoub, Ramy; Miller, Freda; Beera, Kiran; de Medeiros, Cynthia; Laughlin, Suzanne; Bouffet, Eric; Mabbott, Donald
Abstract: OBJECTIVES: Although curative, cranial radiation results in hippocampal insult and memory impairment in children with brain tumours. Metformin stimulates hippocampal neurogenesis and improves memory performance in mice. We conducted a pilot double-blind randomized controlled cross-over trial to examine feasibility and test the effects of metformin versus placebo on hippocampal volume and declarative memory in pediatric brain tumor survivors treated with either focal or whole brain radiotherapy. METHODS: Twenty-four participants (Age = 13.96 ± 3.51) (M=14, F=7) were randomly assigned to complete consecutive 12-week cycles of Metformin (A) and Placebo (B) in either an AB or BA sequence: 10-week washout occurred at crossover. Assessment at baseline and immediately following treatment for each condition included: (a) structural MRI to obtain overall/subfield hippocampal volume and (b) testing of memory encoding/retrieval. Linear mixed modelling was used to test the effects of treatment condition and time on difference from baseline scores: an interaction term was used to test for carryover. FINDINGS: Adherence was high and participants tolerated metformin. No change in overall hippocampal volume was observed bilaterally - but increased volume in the right subiculum and fimbria was evident for metformin vs. placebo (p's < .05). Notably, decreased right CA3 volume was evident for metformin carryover – suggesting a remodeling of hippocampal structure. Treatment with metformin resulted in improved memory encoding immediately and at carryover (p's < .05). CONCLUSION: Metformin may be effective for normalizing hippocampal structure and memory encoding in paediatric brain tumor survivors and warrants consideration in larger trials.